Incidence and treatment results of laryngopharyngeal reflux in chronic obstructive pulmonary disease - OLGUN YILDIZELİ, ŞEHNAZ; ÇELİKEL, TURGAY HÜSEYİN (SPRINGER, 2009)
Laryngopharyngeal reflux (LPR) is defined as the movement of gastric content towards the larynx and the pharynx and it may cause respiratory symptoms or difficulty in their control. We aimed to find the frequency of LPR in chronic obstructive pulmonary disease (COPD) patients and to investigate its effect on COPD symptoms and the results of its treatment. At baseline 30 (20 male, 10 female, mean age: 65 +/- A 10 years) COPD patients completed LPR and COPD symptom questionnaires and 13 (44%) were diagnosed with LPR based on laryngeal examination. Patients with LPR were given 2 months of PPI treatment, after which LPR and COPD symptom questionnaires, laryngeal examinations and pulmonary function tests were repeated. Following the treatment, significant improvements in COPD symptom index, LPR symptom index and laryngeal examination findings were observed in patients with LPR (P < 0.01, P < 0.01, P < 0.0001, respectively). Treatment of LPR resulted in a significant improvement in the symptoms of COPD.
Keywords: Chronic obstructive pulmonary disease; Laryngopharyngeal reflux; Laryngeal examination; LIFE-STYLE FACTORS; GASTROESOPHAGEAL-REFLUX; ESOPHAGEAL FUNCTION; SYMPTOMS; COPD; PREVALENCE; EXACERBATIONS; RELIABILITY; HOARSENESS; VALIDITY